2010
DOI: 10.3340/jkns.2010.48.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Course and Recurrence of Chronic Subdural Hematoma

Abstract: For a working criteria of the recurrence of CSDH, we propose the early recurrence as return of symptoms or reaccumulation of the hematoma after a surgery within 3 months regardless of the location, amount or repeated operations. The late recurrence can be defined as reappearance or enlargement of a liquefied hematoma within the cranial cavity surrounded by the membranes or persistent CSDH beyond 3 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 23 publications
3
48
3
3
Order By: Relevance
“…However, spontaneous resolution of CSDH has rarely been reported, 5 and the reported rate of recurrence after surgery for CSDH is approximately 5%-30%. 13 A few studies have described spontaneous resolution of CSDH. Horikoshi et al 7 reviewed a number of studies and reported that 2.4%-18.0% of cases of CSDH resolved spontaneously without surgical or medical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, spontaneous resolution of CSDH has rarely been reported, 5 and the reported rate of recurrence after surgery for CSDH is approximately 5%-30%. 13 A few studies have described spontaneous resolution of CSDH. Horikoshi et al 7 reviewed a number of studies and reported that 2.4%-18.0% of cases of CSDH resolved spontaneously without surgical or medical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 32 patients required unilateral burr hole drainage (72.7%) and 12 required bilateral operations (27.3%). Among the 44 patients, six patients (13.6%) presented post-operative recurrence in the presence of neurological deficit and CT scan findings [12,16]. The average time to recurrence after burr hole drainage was 36.8 days.…”
Section: Patient Characteristicsmentioning
confidence: 94%
“…15) Treatment for recurrences include percutaneous puncture and aspiration, placement of an Ommaya reservoir, 6,7) a subdural-peritoneal shunt, 6,8) and craniotomy. 6) Endovascular embolization of the middle meningeal artery (MMA) blocks blood that is supplied via the dura to the hematoma outer membrane 9) and is useful as treatment of recurrent CSDH.…”
Section: Introductionmentioning
confidence: 99%